Multiple Modes-Induced Multi-Pair Cross-Phase Modulation Instability in the Deep Normal Dispersion Regime of a Tellurite High Birefringence Microstructured Optical Fiber - Tonglei Cheng; Bin Li; Xiaoyu Chen; Xin Yan; Xuenan Zhang; Fang Wang; Shuguang Li; Takenobu Suzuki; Yasutake Ohishi (IEEE Photonics Journal)
In this paper, multi-pair cross-phase modulation instability (XPMI) induced by multiple modes was experimentally observed in the deep normal dispersion regime of a tellurite high birefringence microstructured optical fiber (HBMOF) fabricated based on 76.5TeO2-6Bi2O3-11.5Li2O-6ZnO (TBLZ) glass. At the pump wavelength of 1062.7 nm three modes were emitted, whose modal birefringence was on the order of >10−5, providing a good platform for the multi-pair XPMI generation. During the experimental investigation, a picosecond laser was adopted as the pump source, and a three-pair XPMI induced by the three modes was observed in the deep normal dispersion regime of the tellurite HBMOF. This work May provide reference for the development of multi-wavelength fiber amplifiers and all-optical modulators.